Clinical and histologic description of ocular anatomy in captive black‐tailed prairie dogs (Cynomys ludovicianus). (19th March 2015) - Meekins, Jessica M.; Eshar, David; Rankin, Amy J.; Henningson, Jamie N.
Abstract: Objective: To describe the clinical and histologic ocular anatomy of the black‐tailed prairie dog (PD). Animals studied: Seventeen captive black‐tailed PDs (11 males and six females), ranging in age from approximately 4 months to 4.5 years. Procedures: Complete ocular examinations, including slit‐lamp biomicroscopy, direct and indirect ophthalmoscopy, were performed under isoflurane anesthesia. The globes ( n  = 2) of one black‐tailed PD were harvested immediately after euthanasia and processed after formalin fixation. Staining with hematoxylin–eosin, cytokeratin AE1/AE3, glial fibrillary acidic protein, chromogranin A, claudin‐5, smooth muscle actin, and vimentin was performed for light microscopic evaluation. Results: A thick mucinous precorneal tear film was present on the ocular surface. A vestigial nictitating membrane was identified in the medial canthus area. The limbus was heavily pigmented, the iris was a dark homogenous brown, and the pupil was round. Funduscopically, there was no tapetum lucidum, the retinal vascular pattern was holangiotic, and a horizontally elongated optic disk was visualized. The most common ocular abnormalities were acquired eyelid margin defects, present in seven eyes of six black‐tailed PDs (35.3%). On histologic examination, the retina was asymmetric, thicker below the optic disk and thinner above it. Conclusions: The black‐tailed PD fundus is atapetal with a holangiotic retinal vessel pattern and a horizontally elongated optic disk. Acquired lesions of the peri‐ocular and eyelid region were the most common documented abnormality. Unique anatomic features of the globe and adnexa were confirmed with histologic and immunohistochemical analysis.